AS AN INTERVENING VARIABLE JOB SATISFACTION AND ORGANIZATION COMMITMENT TO TURN OVER REWARD EMPLOYEES IN ISLAMIC BANKING IN THE BATAM, INDONESIA - Wibisono, Chablullah; Zulva Adi, Ahmad (IJRDO - Journal of Applied Management Science, 2017)
he high rate of employee turnover leads to adverse effects to an organization. Such problem is Likelygenerating instability and uncertainty towards employment condition and human resources cost rise informs of training invested in them, recruitment and newly built training programs. High employeeturnover, in addition, results in organizational ineffectiveness Also Because It loses experiencedemployees as well as spends many times in training new, inexperienced employees. This study aims toanalyze the effect of organizational commitment, turnover intention to reward through worksatisfaction variables and to analyze the most effective variables on turnover intention. According tothe analysis, it is concluded as the followings: organizational commitment has effect on worksatisfaction, reward has effects on work satisfaction,